Modeling of a Microwave Amplifier Operating around 11 GHz for Radar Applications - Mohammed Lahsaini; Lahbib Zenkouar; Seddik Bri (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The low noise amplifier is one of the basic functional blocks in communication systems. The main interest of the LNA at the input of the analog processing chain is to amplify the signal without adding significant noise. In this work, we have modeled a LNA for radar reception systems operating around 11 GHz, using the technique of impedance transformations with Smith chart utility. The type of transistor used is: the transistor HEMT AFP02N2-00 of Alpha Industries®. The results show that the modeled amplifier has a gain greater than 20 dB, a noise figure less than 2 dB, input and output reflection coefficients lower than -20 dB and unconditional stability.